The Holocene transgression in the Golfe du Lion, southwestern France: Paleogeographic and paleobotanical evolution - Aloïsi, Jean-Claude; Monaco, André; Planchais, Nadine; Thommeret, Jean; Thommeret, Yolande (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1978)
Starting from multidisciplinary punctual results, the authors offer a synthesis of lithologie seismic analysis, sedimentology, palynology and radiometrical measurements from sites in sea and at the border of the Golfe du Lion. The dated samples (more than 120) and the variety of the studied sites has permitted a true methodological approach. The authors also propose a curve of the rising of the Holocene sea that takes into account two major facts: the géomorphologie localisation of the site and the characteristics of the sedimentary environment (sedimentary facies and paleobotanic environment). They conclude to: 1) a generalised rapid rise of the transgression since 14,000 years BP, with an acceleration from 8000 to 6000 years BP; 2) intervals of relative stability from 12 000 to 8 000 years BP; 3) a high sea-level at +2 m at around 4500 years BP.